Monitoring and Protection System for Overvoltage, Undervoltage and Unbalance Voltage - Suryono Suryono; Irianto Irianto; Muhammad Saifudin (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2022)
The biggest loss in the industry that caused the industry to experience financial losses that should have been the target of achieving 90% - 100% production was a decrease of up to 40%, due to the production machines not running due to excessive loads used resulting in overvoltage disturbances, voltage drops or unbalanced voltages. To overcome voltage disturbances, a monitoring tool and protection system are needed with a method that can cut off the load automatically when a disturbance occurs, namely by using a contactor as a load breaker from the source and then controlled. using a microcontroller that utilizes relays and voltage sensors. So that the results obtained in the manufacture of tools that refer to SPLN and NEMA then obtained overvoltage disturbances ranging from 399V - 413V, then a voltage drop occurs at 320V - 328V, while the voltage test is not balanced in the R phase which is different from the S phase and T phase, and the percentage of unbalance voltage is 3%, then the tool will cut off the load and it is hoped that from the results that have been carried out it can return the achievement target in the industry.